2010
DOI: 10.1177/0363546510386002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Congruence and Impingement of the Hip Joint in Professional Ballet Dancers

Abstract: The present study indicates that some dancing movements could damage the hip joint, which could lead to early osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
144
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(151 citation statements)
references
References 33 publications
6
144
1
Order By: Relevance
“…Understanding kinematic attributes described by Lamontagne et al [10], Kennedy et al [9], and Charbonnier et al [4,5], it is conceivable that these motions, performed in hips with restricted flexion, can induce shear stresses on the femoral head that can produce the pathologic changes reported here. Whether the specified motions produce shear stresses by causing transient subluxation or forceful nonconcentric motion on the femoral head remains uncertain.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Understanding kinematic attributes described by Lamontagne et al [10], Kennedy et al [9], and Charbonnier et al [4,5], it is conceivable that these motions, performed in hips with restricted flexion, can induce shear stresses on the femoral head that can produce the pathologic changes reported here. Whether the specified motions produce shear stresses by causing transient subluxation or forceful nonconcentric motion on the femoral head remains uncertain.…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, Kennedy et al [9] demonstrated decreased peak hip abduction, decreased frontal ROM, and attenuated pelvic roll in cam-type FAI compared with controls. In a novel motion capture analysis performed in a professional ballet dancer with normal hips, Charbonnier et al [4,5] demonstrated transient subluxation of the hip in certain ballet positions, especially those involving abduction and external rotation in maximum flexion. These findings suggest translational hip motion is associated with FAI.…”
Section: Introductionmentioning
confidence: 99%
“…These extreme positions seem to be responsible for a "pincer-like" mechanism of impingement, with linear contact between the superior or posterosuperior acetabular rim and the femoral head-neck junction. This mechanism has been demonstrated by Charbonnier et al [16,17], who assessed, dynamically, dancers' hip joint motions. Dynamic data were collected by these authors, while the professional dancers were performing six dancing movements: arabesque, développé devant, développé à la seconde, grand écart facial, grand écart latéral, and grand plié.…”
Section: Discussionmentioning
confidence: 74%
“…As reported in Gilles et al [14], the MRI data acquired with the dancers in the splits position showed for the 59 hips a mean femoroacetabular subluxation of 2.05 mm (range 0.63-3.56 mm). The magnitude of subluxation during the dancing movements assessed by Charbonnier et al [16,17] was even greater (peak value = 6.32 mm). We can thus suppose that the lost of joint congruency exposes the dancers' hips cartilage to stress, which also favors cartilage lesions.…”
Section: Discussionmentioning
confidence: 89%
“…While most agree acetabular chondral delamination occurs as a result of shear forces created by the cam deformity [11,23,29,40,46,50,56,62], the cause of defects occurring remotely to the cam or pincer deformity is subject to more speculation. Charbonnier et al [12] demonstrated impingement and secondary femoral head subluxation in dancers with morphologically normal hips, and two studies have demonstrated decreased hip flexion and abduction in patients with FAI [33,36]. It may be that patients participating in sports or vocations that require deeper, forceful, or repetitive hip flexion and rotation subject their cartilage to similar episodes of dynamic instability secondary to their impingement [6].…”
Section: Discussionmentioning
confidence: 99%